The Women’s Personal Autonomy in Richard Yates’s Revolutionary Road - Windya Amalina Safitri (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Abstrak Studi ini menganalisis tentang konsep personal autonomy pada wanita dalam novel Richard Yates yang berjudul Revolutionary Road. Revolutionary Road memiliki latar woman movement pada era 1950-1960 sebagai tema karakter seorang wanita yang memperjuangkan Personal Autonomy sebagai prioritasnya. Dalam penelitian ini menggunakan pendekatan teori Feminism and Personal Autonomy. Sementara itu, dalam Kajian ini menemukan sebuah konsep Personal autonomy pada karakter April Wheeler sebagai wanita yang menetap di wilayah pinggiran Amerika. April adalah seorang wanita yang memiliki perbedaan sudut pandang dan pendapat dalam budaya kehidupan; kemudian dia melakukan sebuah tindakan pemberontakan perbedaan tersebut sebagai wanita minoritas. Study ini menguatkan teori Betty Freidan dan Dworkin dalam hal penggambaran personal autonomy dan kemampuan perempuan dalam mencapai kesejahteraan dan berperan dalam pengambilan keputusan rumah tangga. Kata Kunci : Wanita, Personal Autonomy, Revolutionary Road , Pinggiran Amerika Abstract This study analyzes the concept of personal autonomy in women in Richard Yates's novel, Revolutionary Road. Revolutionary Road has a background for the woman movement in the 1950-1960 era as the theme of a woman's character who fights for Personal Autonomy as her priority. In this study, the theoretical approach of Feminism and Personal Autonomy is used. Meanwhile, this study found a personal autonomy concept in April Wheeler's character as a woman who lives in America's suburbs. April is a woman who has different points of view and opinion in the culture of life. She carried out an act of rebellion against these differences as a minority woman. This study strengthens Betty Freidan and Dworkin's theory in describing women's autonomy and women's ability to achieve prosperity and play a role in household decision making. Keyword(s): Woman, Personal Autonomy, Revolutionary Road, American suburban